(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Until recently in humanity’s history pollution has been considered as a global problem. Along with this growth, there has been an incredible increase in waste by-products. Pollution is typically classified per the type of pollutant by which it’s caused. In general, there are ten different types of pollution, namely, pollution, deforestation, pollution due to reactive waste and radiation, climate changes, acid rains, depletion of the layer, desertification and decline of bio-diversity. Pollution is an undesirable change within the state of water, contaminated with harmful substances. This lands up in the pollution of water whereby the quality of the water deteriorates, affects aquatic ecosystems. Pollution of the water bodies disturbs the ecosystem as a full. Polluted water isn’t only unsafe for drinking and other consumption purposes, but it is also unsuitable for agricultural and industrial uses. The results of pollution are detrimental to groups of individuals, plants, animals, fish and birds. Using it for drinking purpose is that the prime cause for water-borne diseases likes diarrhoea, dysentery and typhoid. This article is enlightening not only pollution and Disease burden due to pollution but also recommending the acceptable steps which should be taken in line with.